The Present Tense Verb Between Nominative, Subjunctive, and Jussive Cases in the Qur’anic Context (A Grammatical and Semantic Study) - Marwa Hawi Ati Al-Abidi, Assistant lecture. (lark, 2026)
This research examines the present tense verb in the Holy Quran by explaining the cases of nominative, accusative, and jussive, while explaining their effect on directing the meaning within the Quranic context. This study aims to highlight the relationship between grammatical structure and meaning, and to show how the tools that enter the present tense verb contribute to changing its temporal and expressive meaning. This is done by following Quranic models in which the present tense verb appears in the nominative, accusative, or jussive cases, and then analyzing them grammatically and semantically according to the requirements of the context within the text of the Quran. The study showed that the nominative case of the present tense verb is often associated with the meaning of permanence, continuity, and renewal, while its accusative case indicates the future, purpose, or reason, and its jussive case is associated with the meanings of condition, prohibition, supplication, and request. The present tense verb carries semantic and rhetorical dimensions that contribute to highlighting the expressive miracle in the Holy Quran. The study proved that the integration between grammar and semantics represents an important approach to understanding the secrets of Quranic expression and the precision of its linguistic structure.